2017
DOI: 10.3390/molecules22050715
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects, SAR, and Action Mechanism of Monoterpenoids from Radix Paeoniae Alba on LPS-Stimulated RAW 264.7 Cells

Abstract: Nine monoterpenoids from Radix Paeoniae Alba, including paeoniflorin derivatives, paeoniflorin (PF), 4-O-methylpaeoniflorin (MPF), 4-O-methylbenzoylpaeoniflorin (MBPF); paeonidanin derivatives, paeonidanin (PD), paeonidanin A (PDA), albiflorin derivatives, albiflorin (AF), benzoylalbiflorin (BAF), galloylalbiflorin (GAF), and debenzoylalbiflorin (DAF), were obtained in our previous phytochemistry investigations. Their anti-inflammatory effects were determined in the present study. The expression and production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…Other studies demonstrated the beneficial effect of Radix Paeoniae on arthritis by inhibiting the proliferation of synoviocytes, leading to decreased production of pro-inflammatory cytokines [47,48]. The anti-inflammatory activity and structure-activity relationship of nine monoterpene derivatives from Radix Paeoniae in LPS-stimulated RAW 264.7 cells were described by Bi et al [49]. Unfortunately, most of the mentioned work did not specifically focus on IFN-γ production.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated the beneficial effect of Radix Paeoniae on arthritis by inhibiting the proliferation of synoviocytes, leading to decreased production of pro-inflammatory cytokines [47,48]. The anti-inflammatory activity and structure-activity relationship of nine monoterpene derivatives from Radix Paeoniae in LPS-stimulated RAW 264.7 cells were described by Bi et al [49]. Unfortunately, most of the mentioned work did not specifically focus on IFN-γ production.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five natural drugs comprising KST, anti‐inflammatory actions have been reported for Cinnamomi cortex , Paeoniae radix , Zingiberis rhizome , and glycyrrhetinic acid and liquiritigenin of Glycyrrhizae radix. In addition, sulfasalazine plus Cinnamomi cortex and Bupleuri radix mixture , paeoniflorin isolated from Paeoniae radix , Glycyrrhizae radix and glycyrrhetic acid isolated from Glycyrrhizae radix have been reported to prevent DSS‐induced ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…According to GO functional annotation, 29,413 unigenes were obtained and categorized into 55 functional groups in three domains including biological process, cellular component and molecular functions (Fig 2C). The biological process category was further classified into 24 groups, metabolic process (15,254 ) and cellular process (14,489) were the predominant groups, followed by singleorganism process (8,816), biological regulation (3,594), localization (3,412) and regulation of biological process (3,063). The cellular component category was further classified into 17 groups, cell (11,981) and cell part (11,901) were the largest two groups, followed by membrane (9,845), organelle (8,516) and membrane part (7,363).…”
Section: Sequencing Reads Filtering and De Novo Assemblymentioning
confidence: 99%
“…So far there are more than 500 cultivars distributed in different regions of China [1]. The dried roots of two herbaceous peony species are the main raw materials for traditional Chinese medicine 'Radix Paeoniae Alba' and 'Radix Paeoniae Rubra' [2,3], which have the functions of antithrombus [4], antitumor [5], anti-post-traumatic stress disorder [6], alleviating inflammation [7], removing pathogenic heat from the blood, treating blood stasis and relieving pain [8] and so on. As an important medicinal plant, herbaceous peony 'Hangshao', which root was the traditional Chinese medicine 'Radix Paeoniae Alba', is mainly cultivated in Zhejiang province, and widely cultivated in China [9].…”
Section: Introductionmentioning
confidence: 99%